2011
DOI: 10.3109/13816810.2011.592175
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus, refractive errors and nystagmus in children and young adults with Down syndrome

Abstract: In our study, the high prevalence of strabismus can not be attributed to the presence of hyperopia. Our data show no association between refraction and strabismus in children with DS. Oblique astigmatism has been found to be the most common type of astigmatism in our study group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 21 publications
(37 reference statements)
4
48
0
1
Order By: Relevance
“…Because Down syndrome patients often have hyperopia [1][2][3][4][5], we allowed several age-matched children with hyperopia to be enrolled in the study, as well as children with emmetropia. The control group had a range of spherical equivalents (−1.75 D to 6.5 D) similar to that in the children with Down syndrome.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Down syndrome patients often have hyperopia [1][2][3][4][5], we allowed several age-matched children with hyperopia to be enrolled in the study, as well as children with emmetropia. The control group had a range of spherical equivalents (−1.75 D to 6.5 D) similar to that in the children with Down syndrome.…”
Section: Participantsmentioning
confidence: 99%
“…Children with Down syndrome are known to be at increased risk for ocular abnormalities, including significant refractive error, strabismus, nystagmus, and even cataracts [1][2][3][4][5]. Poor optical quality at an early age has implications for retinal and cortical image quality.…”
Section: Introductionmentioning
confidence: 98%
“…Japanese children have the same tendency. Moreover, there have been numerous previous reports of hypertropia,2,4,5,810 with the percentage ranging from 1.3 to 8.9. In specific, the superior overelevation in adduction has reportedly been observed in few children,4,5,27 yet it was observed in 39 subjects (44.8%) in this present study and was primarily related to the head tilt, which is one of the important elements in strabismus.…”
Section: Discussionmentioning
confidence: 99%
“…DS subjects also have systemic anomalies and experience delay in development. Several studies have reported that children with DS are afflicted with below-normal visual acuity (VA), as well as refractive error 1024…”
Section: Introductionmentioning
confidence: 99%
“…A pesar que los TO, son los trastornos más recurrentes en nuestra serie (25,7%), son inferiores al 38,47y 60% reportados por Liza-Sharmini 10 , Sandfeld-Nielsen 11 y Stephen E 12 y similar al 26% reportado por Ljubic 13 . Suponemos que esta disparidad se debe al tamaño muestral de los primeros autores en relación al de Ljubic y el nuestro (menos de 70 pacientes vs 176 y 253).…”
Section: Discussionunclassified